Visualize a sua voz : uma proposta para o ensino de ondas sonoras - Moura, Muriel André de (2015)
The present research aims at the development and application, with students from high school, of an educational product for the teaching of sound waves under the discipline of Physics. This educational product, composed of three theoretical classes and one practical one, culminates with the assemblage of an experimental apparatus. That apparatus is easily mounted from low cost materials. It works by detecting the sound waves and converting them in figures alike the Lissajous Figures. In order to evaluate this educational product the Theory of Meaningful Learning from David Ausubel was used, as well as the qualitative research. That way, it was possible to investigate and to collect evidences of meaningful learning by the participating students.